RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN KODULAR PADA MATERI PERUBAHAN BENTUK ENERGI KELAS IV SEKOLAH DASAR - Novita sari; Ahmad Syarif; Issaura Sherly Pamela (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This research aims to describe the development process, level of validity, and level of practicality of interactive learning media assisted by Kodular on the material of energy transformation in grade IV of Elementary School. This research uses the Research and Development (R&D) method with the Lee and Owens development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques are carried out through interview sheets, validation questionnaires by experts, and practicality questionnaires by teachers and students. The results of media validation were carried out in two stages with an average value of 4 with the